2016
DOI: 10.2215/cjn.10551015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Renal Stress/Damage and Filtration Biomarkers with Subsequent AKI during Hospitalization among Patients Presenting to the Emergency Department

Abstract: Background and objectives Emergency departments (EDs) have a growing role in hospital admissions, but few studies address AKI biomarkers in the ED.Design, setting, participants, & measurements Patients admitted to the internal medicine service were enrolled during initial workup in the ED at Robert-Bosch-Hospital, Stuttgart, Germany. Daily serum creatinine (sCr) and urine output (UO) were recorded for AKI classification by Kidney Disease Improving Global Outcomes (KDIGO) criteria. Cystatin C, kidney injury mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…[IGFBP7] for risk assessment of AKI in patients presenting to the ED [18]. In this subanalysis of our ED cohort, we examined the impact of thyroid function, inflammation and obesity on the performance of CysC in a nonintensive care unit (ICU) cohort of patients who presented to the ED.…”
Section: Introductionmentioning
confidence: 99%
“…[IGFBP7] for risk assessment of AKI in patients presenting to the ED [18]. In this subanalysis of our ED cohort, we examined the impact of thyroid function, inflammation and obesity on the performance of CysC in a nonintensive care unit (ICU) cohort of patients who presented to the ED.…”
Section: Introductionmentioning
confidence: 99%
“…We screened 400 patients presenting to the ED of the Robert Bosch Hospital (Stuttgart, Germany) as described elsewhere [12] . Admitted patients at least 18 years of age, with hemoglobin ≥ 9.5 g/ dl (women) or 10.5 g/dl (men), who were capable and willing to sign an informed consent were included.…”
Section: Methodsmentioning
confidence: 99%
“…Most promising are 2 markers of G1 cell cycle arrest, tissue inhibitor of metalloproteinases-2 (TIMP-2) and insulinlike growth factor-binding protein 7 (IGFBP7). Multiple studies have shown that the product of the concentration of these proteins [TIMP-2]·[IGFBP7] in urine is an early indicator of risk for AKI [8][9][10][11][12] . Additionally, urinary [TIMP-2]·[IGFBP7] was recently cleared by the US Food and Drug Administration (FDA) as the first available AKI-biomarker test in the US [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the product of the concentration of these proteins TIMP2·IGFBP7 in urine (Astute Medical, San Diego, CA, USA) is an early indicator of risk for AKI. [23][24][25][26][27][28] As the first available AKI biomarker test in the USA, urinary TIMP2·IGFBP7 was cleared in 2014 by the US FDA. 29 In this study, we tested the hypothesis that urinary TIMP2·IGFBP7 collected directly prior and after PBC administration can predict the development of AKI.…”
Section: Introductionmentioning
confidence: 99%